De sol a sol - Ureña, Jurgen, 1973-; Guidos, José; García, Verónica (Escuela de Cine y Televisión de la Universidad Veritas, 2005)
She wakes up slowly, with a confused feeling between her husband's caress and the sound of the radio. An instant later, she stands up, tides the house a little, takes a bath, eats her breakfast and leaves for work. In the afternoon, she returns, prepares dinner and wakes her partner up. He helps her in some chores, takes a bath, eats and leaves for work. The story is simple and too common. Like them, thousands of couples pass each other briefly and get away every day. In the words of Lichtenberg, when they arrive at their homes, "they do not sleep to dream, but to rest from life." How to tell this love story suffocated under the weight of the daily life? Is it possible to transform it into a text that expresses both silence and separation, absence and boredom? How to face a short story necessarily quiet and contemplative, deprived of the conventional dramatic turns? Is it possible a short film made up of similar routes, comings and goings, deferments and waits? How to express the endless works of Sisyphus? Is it possible? --